Models of innovation management in rye grain production and processing industries of Russia - O. V. Kostenko (Аграрная наука Евро-Северо-Востока, 2018)
Within the open innovation model four applied types of innovation management models can be used in the rye complex of Russia. First, it is creating networking for interaction between industrial and agricultural enterprises. The main types of such networks include technological platforms, innovative networks of universities and scientific institutions as well as interaction models based on crowdsourcing. Secondly, these are models for creating and developing innovation infrastructure. They include innovation funds (Russian Venture Company and second level innovation funds, innovation support programs etc.), technology parks and business incubators, technology transfer centers, etc. Universities and scientific institutions should be the key agents in the modern innovation system. Thirdly, these are small innovative enterprises (SIE) models (with the participation of universities and research institutes). There are four ways to create SIEs. They depend on the type of business, the business owners and their competencies. Fourthly, these are models of strategic partnerships (alliances) between science and business. Formation and stimulation of economic clusters can also be viewed as a complex model of innovation management. Studies of the rye complex in Russian industries have shown that a prominent concentration of the rye grain production and processing industries has been formed on the territory of the Volga Federal District. Three technological chains - food, fodder and technical -form the basis of the rye complex. The technological chains contain a significant number of elements associated with current scientific research. This creates a basis for innovative development and application of the cluster approach.